Radiofrequency Ablation in the Management of Advanced Stage Thymomas: A Case Report on a Novel Multidisciplinary Therapeutic Approach - Panagiotis Paliogiannis; Carlo Pala; Renato Versace; Claudio Pusceddu (Case Reports in Radiology)
We describe in this report a case of successful radiofrequency ablation of an unresectable stage III-type B3 thymoma, and we discuss the role of this novel approach in the management of patients with advanced stage thymoma. The patient, a 59-year-old Caucasian male underwent neoadjuvant chemotherapy with only a slight reduction of the mass. Subsequently, an explorative sternotomy and debulking were performed; before closing the thorax, radiofrequency ablation of the residual tumor was carried out and a partial necrosis of the mass was achieved. A further percutaneous radiofrequency ablation was performed subsequently, obtaining complete necrosis of the lesion. Successively, the patient underwent adjuvant radiotherapy. As a result of this multidisciplinary treatment, complete and stable response was obtained. It is hard to say which of the single treatments had the major impact on cure; nevertheless, the results obtained suggest that radiofrequency ablation must be taken into account for the treatment of advanced stage thymomas, and its effectiveness must be further assessed in future studies.